IMITATION STRATEGIES FOR SME LEARNING PROCESS TOWARDS INNOVATION STRATEGIES - Sulistiyani, Rina; Hadiwidjojo, Djumilah; surachaman, Surachaman; Salim, Ubud (Department of Management, Faculty of Economics and Business, Brawijaya University, 2012)
Imitation is actually a part of innovation strategy, the learning strategies to enter the market. It can be a stepping stone for SME in developing countries to innovate and to create a knowledge base to lower the innovation cost.This study aims to reveal and analyze the innovation strategy learning process by owners of leather small industries processing through experience in running the imitation strategy. This research applies interpretive paradigm, phenomenological research design and involved five informants.The research results are as follow: the learning experience to use imitation strategy which covers stages of imitation, research, development and Â creation. This learning process is the result of interaction between personal and behavior factors, as well as the enabler and barriers. The owners of leather small industries which leave the imitation strategy and switch to innovation strategy are craftsmen who have an entrepreneurial spirit. they are able to balance entrepreneurial and business aspects.